Involvement of clip-domain serine protease in the anti-Vibrio immune response of abalone (Haliotis discus hannai)–Molecular cloning, characterization and functional analysis. Issue 72 (January 2018) - Hu, Jian-Jian; Chen, Yu-Lei; Duan, Xue-Kun; Jin, Teng-Chuan; Li, Yue; Zhang, Ling-Jing; Liu, Guang-Ming; Cao, Min-Jie
Abstract: Vibrio parahemolyticus ( V. parahemolyticus ) is a major pathogen for abalone, an important economical shellfish in coastal area of China. There is little known about the abalone innate immune system against pathogen infection. Clip-domain serine proteases (cSPs) are increasingly recognized to play important roles in host immune defense in invertebrates. In this study, we cloned a cSP (Hdh-cSP) from abalone ( Haliotis discus hannai ). We found out that Hdh-cSP was widely expressed in multiple tissues of abalone, with highest level in the immune-like organ, hepatopancreas. V. parahemolyticus infection induced significantly elevated expression of Hdh-cSP in addition to better-characterized innate immune component genes including Rel/NF-κB, allograft inflammatory factor (ALInFa), macrophage expressed protein (MEP) and caspase-8. Importantly, the silencing of Hdh-cSP reduced the expression of these genes, suggesting that Hdh-cSP was an upstream regulatory factor in V. parahemolyticus infection. Further analysis showed that apoptosis of hemocytes was inhibited when the transcription of Hdh-cSP was knocked down, suggesting that Hdh-cSP participated in cell apoptosis by regulation of caspase 8 expression in V. parahemolyticus infection. Therefore, our study established an important role of cSP in the innate immunity against V. parahemolyticus infection in abalone. Highlights: A clip-domain serine protease (Hdh-cSP) was identified in Haliotis discus hannai. Induced expression of Hdh-cSP was observed after Vibrio parahemolyticus infection. Hdh-cSP regulated the expression of some well-known immune factors. Hdh-cSP was involved in the regulation of hemocytes apoptosis in abalone.